The CDK inhibitor Roscovitine enhances the therapeutic efficacy of anti-PD-1 in non-small cell lung cancer - Diaz-Montero, C. Marcela; Holvey-Bates, Elise G.; Rayman, Patricia A.; Parker, Yvonne; Lindner, Daniel J.; Stark, George R.; De, Sarmishtha (Frontiers in Oncology, 2026)
Immune checkpoint blockade (ICB) targeting the PD-1/PD-L1 axis has significantly improved outcomes in non-small cell lung cancer (NSCLC), yet many patients fail to respond. High PD-L1 expression, often predictive of response, paradoxically correlates with poor prognosis and immune suppression driven by the tumor microenvironment (TME), including myeloid-derived suppressor cells (MDSCs). Roscovitine (Seliciclib), a cyclin-dependent kinase (CDK) inhibitor, downregulates PD-L1 and exhibits immunomodulatory effects, but its potential to enhance ICB efficacy in NSCLC is unknown. Using a syngeneic, immune-competent Lewis lung carcinoma (LLC) mouse model, we evaluated the therapeutic impact of Roscovitine alone or combined with anti-PD-1 therapy. The combination substantially reduced tumor burden, prolonged survival, and induced durable anti-tumor immunity upon tumor re-challenge. Mechanistically, Roscovitine decreased PD-L1 expression on tumor cells and myeloid populations, including circulating and tumor-infiltrating MDSCs, while reducing CCR2+ MDSC frequency in circulation. This was accompanied by increased infiltration of cytotoxic CD8+ T cells and NK cells into the tumor, collectively enhancing anti-tumor immune activity within the TME. These findings demonstrate that Roscovitine potentiates anti-PD-1 therapy by simultaneously suppressing immunosuppressive cell populations and amplifying effector immune responses. The dual modulation of PD-L1 expression and immune cell dynamics provides a strong rationale for the clinical evaluation of Roscovitine in combination with immune checkpoint blockade in NSCLC and potentially other solid tumors.